Delay in loop ileostomy reversal surgery does not impact upon post-operative clinical outcomes. Complications are associated with an increased loss of microflora in the defunctioned intestine. (31st December 2023) - Beamish, Emma L.; Johnson, Judith; Shih, Barbara; Killick, Rebecca; Dondelinger, Frank; McGoran, Ciarra; Brewster-Craig, Caitlan; Davies, Albert; Bhowmick, Arnab; Rigby, Rachael J.
ABSTRACT: Loop ileostomy is a common surgical procedure to allow downstream tissue healing, with the aim of re-joining the bowel approximately 12 months later. The reversal procedure is associated with a substantial morbidity up to 40%. Our previous research demonstrated that defunctioned ileum becomes atrophied, with extensive microbial dysbiosis. This study sought to investigate the potential influence of delaying ileostomy reversal surgery upon both clinical and pathological outcomes. Post-operative clinical data was recorded, including routine blood test results, duration of hospital stay, length of time with stoma and incidence of post-operative complications. We measured ileal fibrosis and atrophy and assessed whether these, or dysbiosis, were impacted by the length of time a stoma was in place, or were linked to clinical outcomes. Associations between clinical data were investigated using scatterplot matrix analysis and t-tests. We found no differences in time between ileostomy formation and reversal in patients experiencing complications vs. individuals with no complications. Furthermore, there were no correlations between days with stoma and pathological measures, such as atrophy or fibrosis, and no ongoing increases in collagen production at the time of reversal surgery. This data suggests that the length of time a stoma is in place does not impact on the likelihood of complications. The incidence of complications is associated with increased loss of microbiota in the defunctioned ileum, but importantly, the decrease in bacteria is not linked to time with stoma. Microbiota diversity in the functional and defunctioned limb correlated within an individual, and was not significantly different between those who experienced complications following surgery vs. those that didn't. Microbiota diversity was also not significantly impacted through delay (>365 days) in stoma reversal. We propose that methods to restore intestinal microbiota numbers, and not necessarily their composition, prior to reversal should be explored to improve the clinical outcomes of ileostomy reversal surgery.